Vulnerability: Considerations on the Appropriate use of the Term in Bioethics - Tarasco, Martha (Studia Bioethica, 2012)
This paper explores the concept of vulnerability in terms of its potential usefulness in bioethics. In order to do this, the author discusses some definitions and descriptions of the term. Subsequently, the term is compared with the concept of fragility, a concept that seems more appropriate for the circumstances of medical ethics. The nature of the term is dealt with, and examples of how it has been wrongly used are given. Among the incorrect uses, we find the search for “vulnerability” in circumstances in which, from the point of view of a realist philosophy of man and recognition of the patients’ objective good, the concept does not seem to apply.